2022
DOI: 10.1021/acs.jmedchem.2c00204
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Optimization of Pyrrolopyrimidine Derivatives as Selective Disruptors of the Perinucleolar Compartment, a Marker of Tumor Progression toward Metastasis

Abstract: The perinucleolar compartment (PNC) is a dynamic subnuclear body found at the periphery of the nucleolus. The PNC is enriched with RNA transcripts and RNA-binding proteins, reflecting different states of genome organization. PNC prevalence positively correlates with cancer progression and metastatic capacity, making it a useful marker for metastatic cancer progression. A high-throughput, high-content assay was developed to identify novel small molecules that selectively reduce PNC prevalence in cancer cells. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Aiming at antimetastasis, the initial hits underwent secondary assays to select for invasion inhibition while excluding those acting via apoptosis induction, DNA intercalation, general cytotoxicity, or cell-cycle arrest [ 100 ]. By means of this multistage screening protocol, two leads were eventually identified out of 140,800 structurally diverse compounds from the NIH Molecular Libraries Small Molecule Repository (MLSMR) due to their outstanding PNC-disassembling efficiency and low cytotoxicity, thus setting the stage for the ensuing medicinal chemistry campaign [ 101 ].…”
Section: Recent Advances In Anticancer Eef1a-targeting Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aiming at antimetastasis, the initial hits underwent secondary assays to select for invasion inhibition while excluding those acting via apoptosis induction, DNA intercalation, general cytotoxicity, or cell-cycle arrest [ 100 ]. By means of this multistage screening protocol, two leads were eventually identified out of 140,800 structurally diverse compounds from the NIH Molecular Libraries Small Molecule Repository (MLSMR) due to their outstanding PNC-disassembling efficiency and low cytotoxicity, thus setting the stage for the ensuing medicinal chemistry campaign [ 101 ].…”
Section: Recent Advances In Anticancer Eef1a-targeting Agentsmentioning
confidence: 99%
“…Specifically, (1) the N -3 substitution at the subdomain I prefers a linear alkyl chain bearing a hydroxy, ether, or amine, and conformational constraint with a cyclohexyl ring gives rise to the highest potency; (2) the N -7 position at the subdomain II tolerates a benzyl, phenethyl, or 4-methoxylphenyl group, but the presence of an alkyl substituent diminishes the potency significantly; (3) the unsubstituted C5 and C6 phenyl rings at the subdomain III are indispensable for high potency. While deducing the above trends, multi-round optimization finally yielded metarrestin ( 25 ), which possesses a superior selectivity window between PNC reduction and cell viability compared with the classic anticancer drugs doxorubicin and camptothecin (table inset in Figure 5 ) [ 101 ]. The in vitro performance of 25 was smoothly translated into in vivo efficacy in three mouse models of human cancer, where it suppressed metastatic invasion with concomitant reduction in PNC prevalence in the cancer cells of primary and metastasized tumors, offering a remarkable survival advantage to the treated animals [ 100 ].…”
Section: Recent Advances In Anticancer Eef1a-targeting Agentsmentioning
confidence: 99%
“…Based on the experience at NCATS, we believe that developing these education activities requires access to scientists who can provide invaluable first‐hand accounts about the decision‐making processes and the factors beyond the science itself that facilitated a successful outcome for the project. The scientists provided examples of where they had to take informed risks with the research direction and the payoffs these decisions produced with regard to advancing the research, how the collaborating partners were necessary to advance the research from preclinical research to a phase I clinical trial (the current state of the project), how the collaborations were formed and managed, and how these and other scientific and operational strategies that helped to advance this project could be used in other settings 4,20 . Throughout the course, students were asked to reflect on how the translational science principles presented during the course could be applied to their own current and future work activities.…”
Section: Teaching Translational Science Principlesmentioning
confidence: 99%
“…Studies have shown that PNC is highly prevalent in cancers, particularly metastatic tumors, whether in transformed cell lines or the patient’s tumor tissues. PNC prevalence in cancer, defined as the percentage of non-mitotic and non-apoptotic cells containing at least one PNC, is variable and ranges from 5 to 100% [ 11 , 12 , 13 ]. Importantly, the PNC is almost exclusively found in non-hematopoietic solid cancer cells [ 9 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Because the PNC is not present in normal healthy cells and does not involve crucial growth or tumor suppressor pathways, it becomes an ideal target for novel anti-cancer drugs. A novel agent such as ML246 (or metarrestin) can inhibit PNC assembly and thus could disrupt cellular processes that are crucial in maintaining a malignant phenotype [ 12 , 18 , 19 ]. While the PNC has been studied in various adult tumors, very little is known about its presence or function in pediatric tumors.…”
Section: Introductionmentioning
confidence: 99%